PROFIL PENGUASAN BAHASA KOMBAI - Buha Aritonang (Balai Bahasa Sulawesi Selatan, 2011)
Kombai language is spoken by Kombai ethnic in Kombai village, Kouh, Boven Digoul, West Papua. This research isan associative research and the objective of this research is to determine the relationship between independent anddependent variables. In this case, it contents of the relationship between Kombai respondents characteristic and masteryof Kombai language. Independent variables consist offour parts, gender variables (X1), age groups (X2), educationallevels (X3), and occupation (X4). Dependent variable is mastery of Kombai language. This research uses descriptiveand Crosstabs analysis that determine the relationship and closeness of independent and dependent variables. Theresult of four hypotheses, it can be concluded that there is not a relationship between X1, X2, X4 and Y. Meanwhile,there is a relationship between X3 and Y. The closeness of the variables [(X1 and Y), (X2 and Y), (X3 and Y),and (X4 and Y)] are weak and grades of variables are not more than 1. AbstrakBahasa Kombai dituturkan oleh suku Kombai di Kampung Kombai, Kouh, Boven Digoul, PapuaBarat. Penelitian ini adalah penelitian asosiatif dan tujuan penelitian ini untuk mengetahui hubunganantara variabel independen dan dependen. Dalam hal ini, penelitian ini menitikberatkan hubunganantara karakteristik responden Kombai dan penguasaan bahasa Kombai. Variabel independen terdiriatas empat bagian, yaitu jenis kelamin (X1), kelompok usia (X2), tingkat pendidikan (X3), danpekerjaan (X4). Sementara itu, varibel dependen adalah penguasaan bahasa Kombai (Y). Penelitianini menggunakan analisis deskriptif dan Crosstabs untuk mengetahui hubungan dan keeratan variabelindependen dan dependen. Hasil empat hipotesis menyimpulkan bahwa tidak ada hubungan antaravariabel X1, X2, X4 dan Y. Sementara itu, ada hubungan antara X3 dan Y. Keeratan variabeltersebut [(X1 and Y), (X2 and Y), (X3 and Y), and (X4 and Y)] lemah dan nilai variabelnya di bawahangka 1.